Harnessing a Feasible and Versatile ex vivo Calvarial Suture 2-D Culture System to Study Suture Biology - Quarto, Natalina; Menon, Siddharth; Griffin, Michelle; Huber, Julika; Longaker, Michael T. (Frontiers in Physiology, 2022)
As a basic science, craniofacial research embraces multiple facets spanning from molecular regulation of craniofacial development, cell biology/signaling and ultimately translational craniofacial biology. Calvarial sutures coordinate development of the skull, and the premature fusion of one or more, leads to craniosynostosis. Animal models provide significant contributions toward craniofacial biology and clinical/surgical treatments of patients with craniofacial disorders. Studies employing mouse models are costly and time consuming for housing/breeding. Herein, we present the establishment of a calvarial suture explant 2-D culture method that has been proven to be a reliable system showing fidelity with the in vivo harvesting procedure to isolate high yields of skeletal stem/progenitor cells from small number of mice. Moreover, this method allows the opportunity to phenocoping models of craniosynostosis and in vitro tamoxifen-induction of ActincreERT2;R26Rainbow suture explants to trace clonal expansion. This versatile method tackles needs of large number of mice to perform calvarial suture research.